Pengaruh Perubahan Variabel Ekonomi Makro terhadap Perubahan Kesehatan Perusahaan Manufaktur - Umi Murtini; Nathalia Dewi (Fakultas Bisnis UKDW, 2006)
This research examines the influence of macro economicvariables changing toward corporate pedormonce changing and macro economic variables. The value of c.orporate condition counted based on averoge industry of corporate pedormlance.This research uses the model of multiile regression with pooleddata. Dependent variable is the corporate performance changing and independent variables are macro economy variables.The result of this researclt shows that macro economic variablesinfluence the changing of manufocture corporate performance at alpha 1%. The most influence variable towards the changing of corporate performonce is a changing on American dollar toward rupiah.Keywords: corporate performance, financial ratio, and macro economic variables